(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
Nowadays, with a significant growth in the number of organizations, they seeks to increase their competitive advantages as much as possible. One of the effective approaches is knowledge management, through which organizations try to reuse the experiences and knowledge created in their previous projects. Today, many projects are carried out by forces from other nationalities, in which each participating organization operates within complex national, organizational, and information contexts. So, knowledge is transferred between geographically dispersed individuals and organizations, and across cultural and national boundaries. Given these conditions, knowledge management processes, especially the transfer and acquisition of knowledge, are very important. The purpose of the present study is to design a conceptual framework of the contextual factors affecting the knowledge transfer in transnational projects using meta-synthesis method. For this purpose, firstly the previous research has been studied and interpreted the factors which are effective in transferring knowledge from different sources and then analyzed them using the open coding method to propose a conceptual framework